Screening of genes related to intramuscular fat deposition in Qianbei black pigs - MENG Jinzhu; WU Zhenyang; AN Qingming; ZHAO Yuanyuan (浙江大学学报. 农业与生命科学版)
This study was designed to screen out the key genes related to intramuscular fat deposition through detecting the fat contents in longissimus dorsi muscle (LDM) and psoas major muscle (PMM), and explore the differentially expressed genes between the two types of muscle of Qianbei black pigs using high-throughput sequencing technology. Five 12-month-old healthy Qianbei black pigs were slaughtered, and LDM and PMM were collected. Some of them were used to detect total fat content, and the rest were used for total RNA extraction, library constructing and sequencing. The annotation genes were obtained by comparing the obtained unigenes with RefSeq database of pig. The differentially expressed mRNAs were analyzed by DESeq2 1.26.0 software, and moreover gene ontology (GO) and Kyoto encyclopedia of genes and genomes (KEGG) pathway analysis of differentially expressed mRNAs were analyzed by GOseq 1.15.5 software and KOBAS 3.0 software. Quantitative real-time polymerase chain reaction (qRT-PCR) was used to verify the candidate genes related to fat deposition. The results showed that the fat content in the PMM was significantly higher than that in the LDM (P＜0.01). A total of 162 differentially expressed genes were obtained by high-throughput sequencing, of which 66 were up-regulated and 96 were down-regulated. Six differentially expressed genes associated with fat deposition were screened out by GO, KEGG analysis combined with the function searching. qRT-PCR results showed that the expression of LPL, PPARA, COX2, PRKAG2 and SCD existed in significant differences between LDM and PMM. The above results lay a foundation for exploring the molecular mechanism of intramuscular fat deposition in Qianbei black pigs, and further provide an experimental basis for the protection, development and utilization of Qianbei black pigs.